IMPLEMENTASI SEKOLAH RAMAH ANAK (SRA) DALAM MENCEGAH TINDAK KEKERASAN TERHADAP ANAK (STUDI KASUS DI MIN 3 JOMBANG) - Mahsun, Ali; Suwandi (Al Tadib : Jurnal Ilmu Pendidikan, 2019)
Abstract: This study aims at explaining the implementation of Child Friendly School (CFS)programs at MIN 3 Jombang. This study uses qualitative descriptive research. The subjects arethe principal, teachers, students, and parents of students with the object of the study covering theimplementation of the Child Friendly School Program at MIN 3 Jombang. Methods of collectingdata in the form of observation, interviews, documentation. Data reduction, data presentation,verification/conclusion drawing are used to analyze data. The results shows: (1) Communication,the dissemination of Child Friendly School Programs to all stakeholders; (2) Human resourcesand infrastructure facilities that support the implementation of Child Friendly School Programsand financial resources that take from BOS funds; (3) Disposition, the existence of a positiveattitude and the commitment to continue implementing the Child Friendly School Program atMIN 3 Jombang; (4) Bureaucratic structure, organizational structure of Child Friendly SchoolPrograms adapted to School Organizational Structure. The learning model used in MIN 3Jombang is Child Friendly Teaching Model (CFTM) which is based on the 3P concept namelyProvision, Protection, and Participation. The supporting factors are human resources,infrastructure facilities, and financial resources that support the implementation of ChildFriendly School Programs and the inhibiting factor is the environmental conditions of thecommunity, especially food sellers outside the school who sell food and beverages that do notmeet hygiene standards. and health for children. Keywords: Program implementation, Child Friendly Schools (SRA), child abuse